Socioeconomic Background Influence on Youth Participation in Internet Crime: The Benin Evidence - Longe, Joshua Sunday; Omigie, Godson Godwin (NIU Journal of Social Sciences, 2025)
Charity begins at home, a parlance which suggest that social experience is never developed in isolation. However contestable, an individual disposition remains a function of his/her background. This paper therefore investigates the relationship between parental socioeconomic background and youth participation in internet crime in Benin City, Nigeria. Using a cross-sectional survey of 1,093 young adults, and in-depth interview with key personalities, the study explores how parental income, education, and family structure influences youth behaviour, propensity and predisposition to internet crime. Anchored on Relative Deprivation Theory, the study finds that although youths engage in internet crime, socio-economic conditions and family dysfunction are an indirectly influence that shapes such behavioural tendencies while pointing that deprivation and societal glorification of wealth act as motivating factors. The study concludes that addressing youth unemployment, improving parenting quality, and reshaping societal values are crucial in mitigating internet crime in Benin City. Keywords: Youth, Background, Socio-economic, Internet Crime.